BORDERS OF NATURE. THE NATURE OF THE POLISH-GERMAN BORDER IN THE PERSPECTIVE OF IMAGOLOGY - Praczyk, Małgorzata (Porównania, 2018)
The political decision concerning the reallocation of the national border resulted in many consequences, among them – the most dramatic consisting in the resettlement of people. The necessity of creating a sense of national community in the new lands triggered many different activities both in the political and social spheres. The appearance of Poles on the so called Regained Territories after World War II was related to the need of endowing it with meanings that would legitimate its Polishness. The writings of historians, geographers, linguists, economists and eventually biologists which were published in years following the war demonstrate the ways and manners of the inclusion of physical space and nature into the imagined realm of the Polish nation. The deconstruction of narrations regarding nature with special attention to the Polish-German border on the river Oder helps to analyze the inseparable connection of natural and historical arguments as conditioning the constitution of the Polish national identity after World War II.